Acetone Gas Sensing Properties of Au-activated Ni-doped ZnO Nanoparticles Prepared by Coprecipitation Method. Issue 6 (June 2018) - Jinxiao, Wang; Jun, Yang; Ning, Han; Jianfeng, Yang
Abstract: Pure and Ni-doped ZnO were prepared by a coprecipitation method, and the gas sensing properties were compared using 20 μg/g acetone. The results show that the optimal Ni doping concentration is 1 mol% with the highest response of 12 μg/g to 20 μg/g acetone. On this basis, Au was decorated onto Ni-doped ZnO to further improve the gas response. The results show that 0.03 mol% Au activated 1 mol% Ni-doped ZnO has the highest acetone gas response (about 17 μg/g to 20 μg/g) in all sensors, and it also maintains high selectivity over ethanol, formaldehyde and benzene, and rapid response-recovery time of <10 s.